The seasonal occurrence of the Whale Shark Rhincodon typus (Smith, 1828) (Orectolobiformes: Rhincodontidae) along the Odisha coast, India - Shesdev Patro; Biraja Kumar Sahu; Chandanlal Parida; Madhusmita Dash; K.C. Sahu (Journal of Threatened Taxa, 2017)
This article gives a description about the seasonal occurrence of Whale Shark in the southern Odisha coast by taking into account of the current observed data and published literatures. The present report claims the sighting of whale sharks during offshore surveys on 13th March 2016 and 15th March 2016, 8 km (19° 15’ 38” N, 85° 01’32” E) and 4.5 km (19º 15’ 69” N, 85° 00’ 58” E) off the coast of Gopalpur Port, Odisha respectively. Most of the earlier reports of whale shark sightings along Odisha coast are from the coastal waters off Rushikulya river mouth or Gopalpur during the month of February-March. Continuous records of whale sharks along southern Odisha coast during February and March suggest the probability of seasonal migration of this giant fish during the period.